2014
DOI: 10.1097/sle.0b013e31828f6ce0
|View full text |Cite
|
Sign up to set email alerts
|

Hand-assisted Laparoscopic Colectomy for Colovesical Fistula Associated With Diverticular Disease

Abstract: To evaluate the feasibility and short-term outcome of hand-assisted laparoscopic colectomy (HALC) for the treatment of colovesical fistula complicating diverticulitis, we reviewed the files of all 34 patients who underwent surgery for diverticular colovesical fistula in 1999 to 2010 at a major tertiary medical center. Twenty-one were treated with HALC and 13 with open colectomy. There were no differences in demographic parameters among the groups. HALC and open colectomy had similar operating time. HALC was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…Additionally, it has been reported that the postoperative stay is significantly shorter for hand‐assisted laparoscopic colectomy than for OS for diverticular disease . This is likely because the tactile perception during hand‐assisted laparoscopic colectomy facilitates dissection of the firm adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been reported that the postoperative stay is significantly shorter for hand‐assisted laparoscopic colectomy than for OS for diverticular disease . This is likely because the tactile perception during hand‐assisted laparoscopic colectomy facilitates dissection of the firm adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…All the studies were retrospective, and were published between 2014 and 2020. [29][30][31][32][33] The pooled sample size of the study was 227 patients, of whom 94 patients underwent open surgery and 133 laparoscopic surgery. The age of the patients in the included studies ranged from 57 to 70 years in the open surgery group, and from 56 to 71 years in the laparoscopic (Table 2).…”
Section: Description Of Included Studies and Patient Characteristicsmentioning
confidence: 99%
“…The laparoscopic technique was detailed in three studies. 29,30,32 Regarding laparoscopic ports, one study employed five ports, 30 another employed four ports, 32 and one study employed handassisted laparoscopic surgery. 29 Vascular pedicles were treated with vascular staplers, 29,30 or vessel sealing devices.…”
Section: Surgical Techniquementioning
confidence: 99%
See 2 more Smart Citations